Hubungan Tingkat Depresi Dengan Tingkat Konsumsi Energi, Protein dan Status Gizi Lanjut Usia di Panti Wreda Surakarta - , Hartini; , Muwakhidah, SKM, M.Kes; , Mutalazimah, SKM., M.Kes (2013)
Geriatric is the phase of life every individual will pass through. Health condition of geriatric people will be high determined by the quality and quantity of nutritional substance intake. Nutritional substance intake affects the nutrition status. Depression is the most mental disorder problem of geriatric. Depression contributes to decrease nutrition intake. The aim of research is to investigate the relationship of depression level and energy intake, protein, and nutrition status of geriatric in Panti Wreda Surakarta. This study is descriptive observational research with cross sectional approach. The sample size was 35. The data collected with simple random sampling technique. The data collection for sample energy, protein intakes was done by visual comstocks for three days in the morning, afternoon and evening. Data of nutritional status was obtained by measuring anthropometry based on IMT. Data of depression level was obtained by measuring the sample depression level using Geriatric Depression Scale (GDS). The statistic tests were Pearson's Correlation Product Moment and Rank Spearman Correlation. The result of this research showed that 60% respondent has normal energy intake ,and 51.4% has deficit protein intake. 48.6% respondent has undernutrition. 74,3% respondent has lower depression category, it is the most depression that appear in this research. There was a relationship of energy intake to nutrition status (p value = 0.001), and protein intake to nutrition status (p value = 0.00). There was no relationship between the depression level to energy intake (p value = 0.535), depression level to protein intake (p value = 0.365), and depression level to nutrition status (p value = 0.702). It was recommended for the personnel of panti wreda to varieted menu and count nutrition value to geriatric nutrition requirement and also pay attention to geriatric pshycological condition. The next researcher will study the relationship geriatric depression level to another nutrient intake.